The Impact of Immigrant Peers on Native Students' Academic Achievement in Countries Where Parents of Immigrants Are Relatively Skilled - Kelvin Seah (Institute for the Study of Labor (IZA), 2016)
This study examines how exposure to immigrant students affects the academic achievement of native students in the three largest immigrant-receiving countries – United States, Australia, and Canada. Using a large cross-country dataset, variation in the share of immigrant children between different grade levels within schools is exploited to identify the impact of immigrant peers. I find that exposure to immigrant children has dissimilar effects on native students' achievements across the three countries. While exposure has a positive impact on Australian natives, it has a negative impact on Canadian natives. Exposure has no effect on U.S. natives. More importantly, I find that institutional factors, such as the way in which countries organise their educational systems, have a crucial bearing on how immigrant students affect their peers.
Keywords: I21; J15; 330; academic achievement; immigrant children; peer effects; within-school estimation